2021
DOI: 10.3390/pr9050797
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel and Other Value-Added Products from Bio-Oil Obtained from Agrifood Waste

Abstract: Bio-oil is a promising source of chemicals and renewable fuels. As the liquid phase obtained from the pyrolysis of biomass, the composition and amount of bio-oil generated depend not only on the type of the biomass but also on the conditions under which pyrolysis is performed. Most fossil fuels can be replaced by bio-oil-derived products. Thus, bio-oil can be used directly or co-fed along with fossil fuels in boilers, transformed into fuel for car engines by hydrodeoxygenation or even used as a more suitable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…Biodiesel produced from algae has advantages over its production from plants, some of which are mentioned. The need for large areas for large-scale cultivation of plants for biodiesel production and the water shortage crisis are important reasons to pay attention to new sources such as algae for biodiesel production [83]. Microalgae are able to absorb CO 2 directly from the gases emitted from power plants and factories, and produce significant volumes of biomass and oil using light and quantitative nutrients [84].…”
Section: Use Of Algae In Biofuel Productionmentioning
confidence: 99%
“…Biodiesel produced from algae has advantages over its production from plants, some of which are mentioned. The need for large areas for large-scale cultivation of plants for biodiesel production and the water shortage crisis are important reasons to pay attention to new sources such as algae for biodiesel production [83]. Microalgae are able to absorb CO 2 directly from the gases emitted from power plants and factories, and produce significant volumes of biomass and oil using light and quantitative nutrients [84].…”
Section: Use Of Algae In Biofuel Productionmentioning
confidence: 99%
“…The literature review addresses the value chain as a ploy made by a company to an existing product's shape, timing, or location to increase its marketability. In agriculture, added value is defined as increasing the economic value of a product, such as wheat, by processing it into another product, such as flour, that the customer requires for baking bread (Sánchez-Borrego et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It represents an opportunity to produce green monomers and other green chemicals, specifically petrochemicals, as Kubicka et al [5] indicated. Besides the hydrotreatment of vegetable oils, significant attention was paid to hydrotreatment of oil (tar) originated from biomass pyrolysis [6][7][8][9]. Derived hydrogenate expresses similar properties as HVOs prepared from primary biomass.…”
Section: Introductionmentioning
confidence: 99%